The Dynamics of Fitopankton Abundance Lake Tepian Batu Teratak Buluh Village, Kampar Regency Riau Province - Magdalena Fitriani Daeli; Madju Siagian; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract The research of phytoplankton abundance dynamics conducted in June-July 2019 at Lake Tepian Batu. A study aims to know the dynamics of phytoplankton abundance. There were 3 stations namely stasion 1 (inlet area), station 2 (in the middle of the lake) and station 3 (in the end of the lake). In each stations, there were 2 sampling point, in the surface and 2 Secchi depth. Sampling was done 4 times, once/week. Water quality parameters measured were temperature, pH, transparency, dissolved oxygen, free carbondioxide, nitrate, phosphate.Result shown that, temperature 28.75-30.50C, pH 5-5.5, transparency 56.5-63.7 cm, DO 3.13-5.35 mg/L, CO26.00 -12.99 mg/L, nitrate 0.031-0.075 mg/L, phosphate 0.062-0.116 mg/L, phytoplankton abundance at the surface range106,990-258,422 cell/L, and 2 Secchi depth range101,229-153,901 cell/L. Temporal and spatial dynamics of phytoplankton at Lake Tepian Batu were influenced of water quality dynamics such as transparency, nitrate and phospate concentration. Keywords:Dynamics, Phytoplankton, Water Quality, Lake Tepian Batu